The Global Challenge of Academic Integrity - Denisova-Schmidt, Elena (International Higher Education, 2016)
The lack of academic integrity is a huge problem at many universities around the world. International students seem to be more frequently involved in various types of cheating compared to domestic ones. This paper discusses some possible reasons for academic dishonesty and shows some successful remedies from different countries.